Enhancing Public Transit Ridership through Mixed Use: A Case Study of Pulo Gebang Terminal - Schouten, Femmy Sofie; Montanasyah, Popik; Amin, Avi Mukti (FOUNDAE (Foundation of Advanced Education), 2025)
Pulo Gebang Terminal, the largest bus terminal in Indonesia and Southeast Asia, continues to face challenges in attracting ridership. Despite its modern infrastructure, passenger levels remain relatively low due to concerns about safety, comfort, and competition from private vehicles. This study aims to identify and propose effective strategies to increase ridership through a mixed-use development approach. Using a quantitative descriptive design combined with qualitative insights, the research employed stakeholder interviews, user surveys, direct observations, and secondary data analysis. The SWOT analysis revealed both internal strengths, such as the integration of health and administrative services, and external opportunities, such as the use of multipurpose spaces, alongside critical weaknesses related to security and service quality. Findings indicate that developing multifunctional facilities, including retail, offices, hotels, entertainment venues, and essential public services, can enhance user comfort, improve service quality, and strengthen the terminal’s integration with its surrounding urban environment. The study contributes to the discourse on sustainable transit-oriented development by demonstrating how mixed-use terminal design can increase ridership while optimizing urban land use. The results provide practical recommendations for policymakers and terminal managers in enhancing Pulo Gebang’s role as a key transportation hub and multifunctional urban center.